INTERNALISASI NILAI KERUKUNAN UMAT BERAGAMA OLEH GURU PAK DALAM MEMPERKUAT SOLIDARITAS SOSIAL SISWA - Saingo, Yakobus Adi; Kasse, Simon; Ali, Umar; Bunga, Agustinus (LPPM Institut Pendidikan Nusantara Global, 2023)
The purpose of this study was to find out the internalization of the value of religious harmony by PAK teachers in strengthening the social solidarity of Grade VIII students at SMP Negeri 1 Soe. This study used a qualitative method where primary data was collected through interviews with 5 PAK teachers and 5 students from class VIII SMP Negeri 1 Soe as respondents using the FGD (Focus Group Discussion) approach. The data that has been collected is then analyzed and discussed using a descriptive approach. The results of the study show that the internalization of the values ​​of religious harmony has been manifested in every lesson by PAK teachers at SMP Negeri 1 Soe through teaching and education related to living the values ​​of tolerance, equality, and building cooperation with other friends regardless of background religious beliefs. In addition, the values ​​of inter-religious harmony that have been instilled as a whole and as a whole are able to have an impact on the strengthening of social solidarity among students at SMP Negeri 1 Soe which is shown by mutual trust, mutual respect, responsibility for the common good, paying attention to the interests each other despite living in religious pluralism.